2017
DOI: 10.1039/c7cp02306e
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature sintering of polar ZnO nanosheets: I-evidence

Abstract: During storage the ZnO crystals grew mainly by the partial merging of their polar surfaces in a process triggered by the action of moisture, oxygen and, in the absence of these two agents, light.The mechanism of this intriguing phenomenon will be analyzed in detail in the second part of this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 29 publications
(45 reference statements)
3
32
0
Order By: Relevance
“…Since the surface energy is minimum along the (002) direction, its growth rate will be comparatively lower than the high surface energy (100) and (101) orientations. Furthermore, the (002) orientation exhibits a more polar nature than the (100) and (101) which facilitates the charge carrier separation and surface reactivity . The polarity of ZBO structures can be evaluated using the intensity ratio (I 002 /I 100 ) of the XRD data and has been found to be increased with the increase of Ba content due to more polarity on Ba−O bond .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the surface energy is minimum along the (002) direction, its growth rate will be comparatively lower than the high surface energy (100) and (101) orientations. Furthermore, the (002) orientation exhibits a more polar nature than the (100) and (101) which facilitates the charge carrier separation and surface reactivity . The polarity of ZBO structures can be evaluated using the intensity ratio (I 002 /I 100 ) of the XRD data and has been found to be increased with the increase of Ba content due to more polarity on Ba−O bond .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the (002) orientation exhibits a more polar nature than the (100) and (101) which facilitates the charge carrier separation and surface reactivity . The polarity of ZBO structures can be evaluated using the intensity ratio (I 002 /I 100 ) of the XRD data and has been found to be increased with the increase of Ba content due to more polarity on Ba−O bond . Thus this preferential orientation along the c – direction is useful in piezoelectric applications and other optoelectronic applications such as photovoltaic devices, photodetectors and sensors …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first part of this work [1] it was concluded that polar ZnO nanosheets of high specific surface area (~120 m 2 /g) lost up to 75% of their specific surface area in about two months during their storage in closed transparent polypropylene vials kept under the light of the laboratory on worktop tables. Loss of surface area occurred in parallel with the growth of nanocrystals, mainly by the partial merging of their polar surfaces at the expense of the small mesopores (~5 nm pore size) initially present in the nanosheets.…”
Section: Introductionmentioning
confidence: 99%